Change Over Time in Brain Serotonin Transporter Binding in Major Depression: Effects of Therapy Measured With [(123)I]-ADAM SPECT - Amsterdam, Jay D. (J Neuroimaging, 2013)
Several studies have reported low brain serotonin transporter (SERT) binding in individuals with major depression. We hypothesized that the SERT standardized uptake ratio (SUR) values using [(123)I]-ADAM single photon emission computed tomography would increase in depressed subjects who responded to cognitive behavior therapy (CBT) compared to CBT nonresponders. [(123)I]-ADAM scans were acquired before and after 12 weeks of CBT from 20 depressed subjects and on two occasions 12 weeks apart from 10 non-depressed, healthy volunteers. The primary outcome measure was change over time in SUR values in the midbrain, medial temporal lobe, and basal ganglia regions. Depressed subjects demonstrated low pre-treatment mean SUR values that significantly increased over time in the midbrain (p=0.011), right medial temporal lobe (p=0.008), and left medial temporal lobe (p=0.000) regions. Treatment responders showed a significant increase over time in SUR values in left medial temporal lobe (p=0.029) and right medial temporal lobe (p=0.007) regions. Partial and nonresponder subjects also showed a significant increase over time in SUR values in the left medial temporal region (p=0.040) (versus healthy volunteers), but to a lesser degree. The findings suggest that low pre-treatment SERT binding may increase over time in some depressed individuals who experience symptom improvement.